(untitled) (Research, Society and Development, 2022)
This study aimed to identify positive cases of fecal occult blood and correlate with the presence of intestinal parasites in stool parasitological examinations (PE). Sample collections were carried out at the home for the elderly in the city of São José do Egypt-PE, a sample composed of 20 elderly people aged > 60 years, of both sexes. To perform the fecal occult blood test, the immunochromatography technique was used, the analysis of the PE was applied to the Hoffman Technique. The study observed the absence of blood in the feces of the elderly (100% negative tests), however in the analyzed EPFs, 45% of the elderly had some type of protozoa, with the male gender being the most positive (66.7%). The protozoan species found were Endolimax nana cysts (54.5%), Giardia lamblia (18.2%), Entamoeba coli (18.2%) and Entamoeba histolytica / dispar (9.1%). It was concluded that this institution has an almost zero incidence of parasitological risk, because due to a great rigor in food and personal hygiene and a wide conserved geographical space, the factors that allow a better living condition for the inmates are preserved by the nursing home.